The implications of divorce in psychoantic development in first childhood in the psychoanalytic perspective (Research, Society and Development, 2019)
This qualitative and exploratory study aims to understand the implications of the conjugal separation in the psychic development of children from 0 to 6 years in the psychoanalytic perspective of Freud and Winnicott in order to verify the implications of divorce in the psychic development of children from 0 to 6 years from Psychoanalysis. It has been found as a result that children may experience feelings of abandonment, guilt, parental or aggressive fantasies of reconciliation, undergo oedipal reorganization and can often be placed by parents in a position which can not meet the demand. It was concluded that children should continue to receive attention, affection and being narcissistically invested by both parents, that divorce is a time of crisis, however, the implications of marital separation depend very much on the behavior of parents toward the child and the relationship between them.